2019
DOI: 10.1002/ejp.1480
|View full text |Cite
|
Sign up to set email alerts
|

Change in fatigue in acceptance and commitment therapy‐based treatment for chronic pain and its association with enhanced psychological flexibility

Abstract: Purpose Fatigue is commonly reported by people with chronic pain. The purpose of the current study was to examine Acceptance and Commitment Therapy (ACT), based on the Psychological Flexibility (PF) model, for fatigue in chronic pain. Methods This study included 354 adults attending an interdisciplinary ACT‐oriented treatment for chronic pain. T‐tests and analyses of clinically meaningful change were used to investigate participant improvements in fatigue interference after the treatment. Pearson's correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…Depressive symptoms were measured using the Japanese version [ 40 ] of the Patient Health Questionnaire-9 (PHQ-9) [ 43 ]. The PHQ-9 has been used to treat depressive symptoms in individuals and patients with chronic pain [ 17 , 22 , 24 , 26 , 30 ]. The Japanese version is strongly correlated with another scale designed to measure depressive symptoms [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressive symptoms were measured using the Japanese version [ 40 ] of the Patient Health Questionnaire-9 (PHQ-9) [ 43 ]. The PHQ-9 has been used to treat depressive symptoms in individuals and patients with chronic pain [ 17 , 22 , 24 , 26 , 30 ]. The Japanese version is strongly correlated with another scale designed to measure depressive symptoms [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, accumulating evidence suggests that psychological inflexibility is associated with higher levels of depressive symptoms in individuals with chronic pain [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Additionally, ACT for chronic pain alleviates depressive symptoms by improving psychological inflexibility [ 22 , 25 , 26 , 27 , 28 , 29 , 30 ]. One study [ 31 ] found that psychological inflexibility predicted severe depressive symptoms in 144 patients with chronic pain, independent of the effect of their pain intensity, mindfulness, and pain-related acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of chronic pain, the independent variable is usually pain, and the dependent variables are pain interference, depression, anxiety, etc. [ 40 ], even when other aspects, such as fatigue, are already being considered [ 41 ]. However, fibromyalgia is a syndrome in which pain is not the only or the main symptom.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a call for contextually sensitive approaches to behavioural determinants of functioning in chronic pain has been made (Yu et al., 2020). The development of the Activity Patterns Scale has been a first step in this direction (Esteve et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this activity pattern was only significantly related to depressive levels when pain severity levels were at their highest (M = 10). In recent years, a call for contextually sensitive approaches to behavioural determinants of functioning in chronic pain has been made (Yu et al, 2020). The development of the Activity Patterns Scale has been a first step in this direction (Esteve et al, 2016).…”
Section: Multivariate Associations and Moderation Analysesmentioning
confidence: 99%